Safety and efficacy of AviPlus® as a feed additive for turkeys for fattening, turkeys reared for breeding and suckling piglets. (25th July 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on an application for the authorisation of AviPlus ®, an additive containing a mixture of sorbic acid, citric acid, thymol and vanillin, for use in turkeys for fattening and for breeding at a recommended dose range of 200–500 mg/kg complete feed and in suckling piglets at 1, 000–3, 000 mg/kg complete feed. AviPlus ® is considered safe for turkeys for fattening and turkeys reared for breeding up to the maximum recommended dose of 500 mg/kg complete feed. For suckling piglets, the additive is safe up to the maximum recommended dose of 3, 000 mg/kg complete feed. The additive is considered safe for the consumer and the environment. The additive is considered a potential skin/eye irritant and a skin sensitiser. The additive has the potential to be efficacious as a zootechnical additive in turkeys for fattening, turkeys reared for breeding at a minimum dose of 200 mg/kg complete feed. For suckling piglets, AviPlus ® has the potential to be efficacious at a minimum dose of 1, 000 mg/kg complete feed.